(untitled) (Revista de Ciências Agroveterinárias, 2018)
The experiment aimed to test the crop selectivity and postemergence weed control on common beans. The treatments consisted of cloransulam, and imazethapyr isolated and tank-mixed with bentazon, a weedy control and a weed-free control for comparison of the cultivars Agronorte (ANfc9) and IPR Uirapuru of common beans. The experiment was conducted on a field, on a complete randomized block experimental design with four replications. The variables analyzed were crop injury, weed control, first pod height, pod number, 1000 grains weight and crop yield. Each cultivar behaves differently with the ALS herbicides. The cultivar ANfc9 was more tolerant to the ALS herbicides than IPR Uirapuru. Bentazon tank-mix with cloransulam or imazethapyr decreased the level of crop injury and no antagonism was observed to weed control.